Atomic power : An appraisal including atomic energy in economic development - Allardice, Corbin; Dunworth, J. V.; Sporn, Philip (New York: Pergamon Press, 1957)
This volume begins with a series of notes on "the atom", "atomic energy", "radioisotopes" and related subjects.
International series of monographs on the economic aspects of nuclear energy.
ne 10/05/2018
Loans
Keywords: Nuclear Energy; Atomic power; Economic development - energy